The Role of Psycholinguistic in Understanding Language Learning Errors - Hasyanah, Hafifah; Nasution, Tuti Alawiyah Ramadani; Lestari, Dwita; Lubis, Yani (Jurnal Pendidikan Tambusai, 2025)
This study investigates the role of psycholinguistics in elucidating the underlying cognitive mechanisms that give rise to language learning errors in second language acquisition. Rather than viewing errors as mere deviations from target language norms, this study interprets them as manifestations of mental processes activated during language comprehension and production. Employing a qualitative documentary research design, this investigation synthesizes findings from scholarly books, journal articles, and previous empirical studies related to psycholinguistics and error analysis. The analysis reveals that lexical, grammatical, and phonological errors frequently emerge due to constraints in lexical retrieval, phonological encoding, working memory capacity, and the developmental nature of interlanguage. The findings further demonstrate that language errors follow systematic patterns shaped by interactions among first-language influence, incomplete internalization of second-language rules, and cognitive processing limitations. This study concludes that psycholinguistic perspectives offer a comprehensive and explanatory framework for understanding the mental operations that contribute to the emergence, recurrence, and potential fossilization of learner errors. These insights provide valuable implications for instructional practices that aim to address the cognitive origins of learners’ difficulties in second language development.